Peran inhibitor HMG-CoA reduktase dalam penurunan Interleukin6 terhadap hasil akhir klinis penderita kontusio serebri - Sabri Ibrahim; Rr. Suzy Indhary; Iskandar Japardi (Majalah Kedokteran Nusantara The Journal Of Medical School, 2012)
Background : The cascade of dead cells in response of secondary brain damage is still a major problem in brain injury managementObject : Evaluate HMG-CoA reductase inhibitor as a neuroprotective agent with IL-6 biomarker, to patients with clinical outcome of cerebral contussionMethods : The authors used prospective experimental research on 50 moderate brain injury patients with cerebral contussion appearance in Head CT - Scan, research was done from May 2011 until July 2012. Respondents were divided into two groups; the first group were treated with standard moderate brain injury therapy and the other group were added with HMG-Co A reductase inhibitor (Simvastatin). As parameter, IL-6 biomarker was tested in the first day and the fifth day weekly. Clinical final results (GOS and Barthel’s) were scored monthly and were also noted when the patients left the hospital. Results : Based on this research, the authors found that GOS score in 1 month period with standard therapy is 4.81 (SD 0.39 and the score in patients with HMG added is 4.90 (SD 0.30). Barthel’s score in 1 month period for standard therapy is 95.00 (SD 7.56) and the score for other group is 96.67 (SD 5.55), slightly higher in patients with HMG added (P = 0.616). Decreasing number on IL-6 was commonly found after therapy was added P = 0.295 for the 1st day and P = 0.834 for the 5th day. The researchers were also found that there was weak positive correlation on IL-6 serum during the 1st day with GOS (r = 0.124, P = 0.444) and Barthel’s (r = 0.029, P = 0.852) for 1 month. From the analysis we found P = 0.187 for GOS in 1 month and Barthel’s in 1 month 0.219 with P >0.05. Therefore, there was no correlation IL-6 serum in the 5th day with GOS and Barthel’s in 1 monthConclusions : There was no significant corelation between HMG-CoA reductase inhibitor and the clinical outcome (GOS and Barthel Index).Keywords : cerebral contussion; IL-6; GOS; Barthel’s Inde